MANAJEMEN KESISWAAN - Mesi Santriati (Manajer Pendididikan, 2020)
The purpose of this research to describe student management that takes place in Public Senior High School Number 4 Kepahiang Regency. This research used descriptive qualitative method. Data taken by interview, observation and documentation study. In this research the subjects of the study were the principal, the deputy headmaster of the curriculum and student fields and several students and study teachers and administrative staff at this school. This research shows that the ongoing student management process is in accordance with the scope of student management, and is prepared by the school in accordance with the technical instructions from the education office.